Suplementação com gordura protegida de óleo de palma na alimentação de vacas leiteiras - Zatta, Marcelo Rodrigo (2014)
Dairy cows need to eat right after childbirth lot of energy to support milk synthesis increases linearly. With the objective of this study was to evaluate the effect of levels of palm oil in protected form as a supplement in the diet of dairy cows on body dynamics, production and milk composition, metabolic profile and reproduction. The experiment was conducted in the months of July and August 2013 in the city of Paraná, Chopinzinho, 27 Holstein cows were used with an average weight of 651 ± 82.7 kg, distributed according to a randomized block design (RBD) according to lactation (0-90 days) and three treatments inclusion levels of protected fat Magnapac ® (Madrid, Spain). The blocks were formed from the average milk production, properly balanced for weight, age, number of offspring. The treatments included the Protected fat of palm oil in the proportion of 0, 250 and 500 g / animal / day. The weight of milk and collection for analysis of chemical composition, as well as blood samples were taken on days 07, 14 and 30 after starting supplementation. Reproductive diagnoses were made on days 0 and 30.Os results of total milk production showed no significant effect (P> 0.05) in relation to different levels of protected fat. On proximate composition of milk parameters, fat, protein, lactose, total solids, nonfat dry extract, urea and somatic cell count had no significant effect (P> 0.05). The metabolic profile variables that showed a linear increase (P <0.05) Total Cholesterol and LDL-Cholesterol other variables, aspartate aminotransferase, gamma-glutamyl transferase, albumin, total protein, urea, alkaline phosphatase, HDL cholesterol and triglycerides did not were affected (P> 0.05). Regarding reproductive part supplementation with fat promoted an increase in pregnancy rate and return to estrus in groups 250 and 500 grams, as well as decreases the amount of cows in anestrus. The supplementation of protected fat of palm oil in the diet of dairy cows proved effective in increasing plasma levels of total cholesterol and LDL - cholesterol, promoting improvements in reproduction, but does not significantly alter milk production and its composition.